2011
DOI: 10.3390/molecules16086432
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Application of SelectfluorTMF-TEDA-BF4 as a Versatile Mediator or Catalyst in Organic Synthesis

Abstract: SelectfluorTM F-TEDA-BF4 (1-chloromethyl-4-fluoro-1,4-diazoniabicyclo [2.2.2]octane bis(tetrafluoroborate) is not only one of the most efficient and popular reagents for electrophilic fluorination, but as a strong oxidant is also a convenient mediator or catalyst of several “fluorine-free” functionalizations of organic compounds. Its applications as a mediator in transformations of oxidizable functional groups or gold-catalyzed C-C and C-heteroatom oxidative coupling reactions, a catalyst in formation of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 81 publications
0
43
0
1
Order By: Relevance
“…This reaction can be considered as an alternative to the regioselective oxidation of the exocyclic sulfur atom of ketene dithioacetal 1 with m‐ CPBA, even if Selectfluor is a much more expensive reagent. Anyway, Selectfluor was previously reported as a powerful oxidizing agent able to easily oxidize sulfur atoms, such as in thioglycosides, into their sulfinyl derivatives in a few minutes …”
Section: Resultsmentioning
confidence: 99%
“…This reaction can be considered as an alternative to the regioselective oxidation of the exocyclic sulfur atom of ketene dithioacetal 1 with m‐ CPBA, even if Selectfluor is a much more expensive reagent. Anyway, Selectfluor was previously reported as a powerful oxidizing agent able to easily oxidize sulfur atoms, such as in thioglycosides, into their sulfinyl derivatives in a few minutes …”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, this active radical species has never been applied in oxygen incorporation reactions. We envisioned that a combination of phenol and Selectfluor6 in the presence of O 2 may produce the superoxide species I and the fluorine radical II ,5, 7 then I might serve as an active O‐transfer agent for organic substrates in the presence of the fluorine radical. Based on this hypothesis, we herein present our recent discovery in the activation of dioxygen by a combined phenol/Selectfluor system and its application in the oxidation‐dimerization of alkynes to access 2‐ene‐1,4‐diones under metal‐free conditions (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…ing a number of photocatalysts (Table 2, entries 9-11), we observed that {Ir[dF(CF 3 )ppy] 2 (dtbpy)}PF 6 gave a much higher yield at 52% compared with Ru(bpy) 3 Cl 2 . Finally, variation of the base to potassium hydroxide ( Table 2, entries [12][13][14] provided an increase of yield to 68%. Interestingly, we noticed a trace amount of a disulfenylated side product 18c when the iridium photocatalyst is used, suggesting that at some point the thiophenol reagent (or product sulfide) is oxidized and reacts with a second equivalent of thiophenol.…”
Section: Cluster Syn Lettmentioning
confidence: 98%